SOCIAL CAPITAL AND FARMERS' DECISION TO CULTIVATE PULU MANDOTI EMAS (PME) LOCAL RICE: A PROBIT MODEL - Saputra, Muhammad Taufik; Mulyo, Jangkung Handoyo; Darwanto, Dwijono Hadi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Salukanan Village, Enrekang Regency, is the production center of inherited local rice through generations, known as "pulu mandoti emas" (PME). The PME local rice has a unique aroma and can exclusively grow in the village of Salukanan, Enrekang Regency. The relatively long cultivation period (six months) drives the farmers neglecting PME cultivation. However, the higher selling price of PME (in average of Rp 72,200/kg) compared to regular rice makes the consumers only purchase it when needed for traditional events (weddings ceremonies, funerals, housewarming ceremonies, etc.). It is suspected that the social capital possessed by farmers influences their motivation to continue cultivating PME. This article aims to analyze social capital (communication frequency regarding PME cultivation with external parties, social trust, institutional trust, and norms of reciprocity) other factors such as socio-economy characteristics and institutional factors that affect farmers' decisions to continue cultivating PME. The study was conducted in Salukanan Village, Enrekang Regency, by collecting data from 96 farmer respondents selected through simple random sampling. A probit model regression analysis was used and the result indicated that strengthening social capital among farmers by improving communication, trust, and reciprocity, along with leveraging their existing experience through mentoring and knowledge-sharing initiatives, can significantly encourage the continued cultivation of PME local rice. Comprehensive support through inclusive policy development, training, counseling services, and active engagement initiatives is essential for sustaining PME local rice cultivation in Salukanan Village.